Active breathing coordinator combines with custom-designed puncture needle improves diagnostic accuracy of ≤20 mm pulmonary nodules under CT-guidance: a real world prospective study - Huang, Yuting; Yang, Jie; Liu, Peisen; Xuan, Jinnan; Xiao, Xin; Wang, Chao; Meng, Fanliang; Mou, Hao; Zhang, Xu; Ji, Shuang (Frontiers in Oncology, 2025)
BackgroundCT-guided percutaneous transthoracic needle biopsy (PTNB) is still the main way for obtaining pathological diagnoses of pulmonary nodules. However, the small size and respiratory-induced motion reduce diagnostic accuracy for patients with small pulmonary nodules (≤20mm). In this study, we aimed to improve biopsy precision and diagnostic accuracy for patients with small pulmonary nodules via introducing significant refinements.Methods122 patients with ≤20mm pulmonary nodules were enrolled and randomly assigned to the ABC-NG PTNB group and CT-guided PTNB group. The CT-guided PTNB group underwent conventional CT-guided PTNB, while the ABC-NG PTNB group received additional ways including thermoplastic immobilization, active breathing coordinator (ABC), and a custom-designed puncture needle. Puncture accuracy, diagnostic accuracy, and complication rates were compared between the two groups.ResultsThe ABC-NG PTNB group was superior to the CT-guided PTNB group in the terms of angle error, craniocaudal plane error, positioning error, diagnostic accuracy, and one-puncture success rate (P < 0.05). The ABC-NG PTNB group had fewer punctures, fewer CT scans, lower radiation doses, and lower incidence of pneumothorax as compared to CT-guided PTNB group (P < 0.05). Furthermore, diagnostic accuracy was particularly enhanced in cases where the puncture angle was non-zero or when the nodules were located in the lower lung lobes (P < 0.05).ConclusionCt-guided PTNB combined with ABC and custom-designed puncture needle guide improves the accuracy and diagnosis rate of ≤20mm pulmonary nodule biopsy, especially nodules are located in the lower lung lobe or require a non-zero puncture angle.